De la notion de juridiction en droit administratif canadien - Amyot, Bernard (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The object of this article considers the ever-evolving concept of jurisdiction in the context of judicial review of administrative action. The author examines recent jurisprudential developments from an historical perspective in an attempt to reveal those factors triggering intervention. The Supreme Court of Canada has often fashioned its tests of jurisdiction to fit the intended results. Hence, over the last decades, jurisdictional terminology has become ripe with deceptive distinctions and attempts to rationalize the various tests have in fact raised most perplexing problems.